2016
DOI: 10.1039/c6ra01511e
|View full text |Cite
|
Sign up to set email alerts
|

Carbide-derived carbon in polypyrrole changing the elastic modulus with a huge impact on actuation

Abstract: While carbide-derived carbon (CDC)-based materials have shown stable behavior in ionic electro-chemomechanical actuators, the displacement and actuation speed have remained low compared to conducting polymer-based actuators. The goal of this research was to obtain more responsive conducting polymer-CDC composite films and to investigate their linear actuation properties, comparing the stress and strain to those of polypyrrole (PPy) doped with dodecylbenzenesulfonate (DBS À ). The PPy-CDC hybrid films were synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…In earlier research, the corresponding decrease in stress on oxidation has been observed in carbide-derived-carbon-PPy hybrid actuators [31]. In the case of carbon-based ionic electromechanical actuators, this behavior has been explained by the two-carrier model, where after cation diffusion out of the material, a small number of anions enter the material, causing expansion [32].…”
Section: Chronoamperometric Isotonic and Isometric Ecmd Measurementsmentioning
confidence: 94%
“…In earlier research, the corresponding decrease in stress on oxidation has been observed in carbide-derived-carbon-PPy hybrid actuators [31]. In the case of carbon-based ionic electromechanical actuators, this behavior has been explained by the two-carrier model, where after cation diffusion out of the material, a small number of anions enter the material, causing expansion [32].…”
Section: Chronoamperometric Isotonic and Isometric Ecmd Measurementsmentioning
confidence: 94%
“…During galvanostatic polymerization, the applied voltage reached the value of 2.2 V in the 2-electrode system [27]. It is notable that the addition of PTA results in lower synthesis potential in the range of 1.4 V [17].…”
Section: Polymerization Of Ppy/dbs and Ppy/dbs-ptmentioning
confidence: 99%
“…Recent research has revealed that PTA was able to embed carbon particles (carbide-derived carbon) during electropolymerization forming PPy/DBS-CDC hybrids, which had increased maximum strain due to changing of the films elastic modulus [27]. The formation of PPy linear actuators (free-standing films) containing PTA as electrolyte has not been reported until now, mostly due to the extreme brittleness of these films.…”
Section: Introductionmentioning
confidence: 99%
“…For each system, three samples were prepared and measured independently. The strips were connected to the force sensor (TRI202PAD, Panlab, Barcelona, Spain) with a fixed arm that served as a working electrode in a linear muscle analyzer set up . A platinum sheet was used as the counter electrode and Ag/AgCl (3 M KCl, +0.23 V vs SHE) as the reference electrode in the measurement cell containing 0.2 M solution of LiTFSI in water and propylene carbonate.…”
Section: Expermentalmentioning
confidence: 99%